1982
DOI: 10.1288/00005537-198205000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory tympanotomy revisited.

Abstract: The history of exploratory tympanotomy is somewhat obscure. Methods and findings of exploratory tympanotomy were described and assessed for unexplained conductive and occasional sensorineural hearing losses. Of 316 recent cases positive findings leading to diagnosis and therapy occurred in all 250 cases of conductive hearing losses and in 43 of 63 cases of sensorineural hearing losses. In decreasing order of occurrence findings were sequelae of otitis media, otosclerosis, oval and round window changes includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Paparella and Koutroupas [11] found the most common diagnosis to be otosclerosis in 79.7%, followed by congenital fixation of the stapes in 10.6%, and he also found 20% of case had sensory neural hearing loss, 29.7 % of case had normal tympanic membrane. He could not find the reason for sensorineural hearing loss in three cases.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Paparella and Koutroupas [11] found the most common diagnosis to be otosclerosis in 79.7%, followed by congenital fixation of the stapes in 10.6%, and he also found 20% of case had sensory neural hearing loss, 29.7 % of case had normal tympanic membrane. He could not find the reason for sensorineural hearing loss in three cases.…”
Section: Discussionmentioning
confidence: 94%
“…[12] Shin et al [13] found that while CT scanning diagnosed 91.3% of cases of otosclerosis, the accuracy was 57% for other minor malformations. Techniques such as laser Doppler vibrometry [11] and wideband energy ref lectance [14] may be of use but their accuracy has yet to be proven in large clinical studies. Decreased anti-measles serum immunoglobulin G may be diagnostic for otosclerosis but does not exclude stapes fixation of other causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such pathological obstruction (e.g., cholesteatoma, granulation tissue, tympanosclerosis, and so forth) or anatomical physiological obstruction can lead to generalized or localized pathological conditions. 1,6,9 An understanding of the inter‐relationship between disease and location dictates the need for a wide surgical exploration.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to distinguish the membrane itself from mucosal folds in the niche (the so‐called false membranes). 8–10 Any loculated collection of fluid should be suctioned; granulation tissue strategically located within the niche should be meticulously addressed and, if possible, removed. The integrity of the round window membrane (as well as the footplate) should never be jeopardized during a first‐stage tympanoplasty or tympanomastoidectomy.…”
Section: Introductionmentioning
confidence: 99%